Synthesis of ZSM-5 Zeolite from low-water/fluoride route for the treatment of petroleum industry effluent - Amosa, Mutiu K.; Al-Khatib, Ma'an Fahmi Rashid; Jami, Mohammed Saedi; Jimat, Dzun Noraini; Owolabi, R. Uthman; Muyibi, Suleyman Aremu (2013)
ZSM-5 crystals have been prepared by Fluoride combined with low-water synthesis route. The zeolite was characterized for high Si/Al ratio (SAR) of 194.4 with good adsorption and catalytic prowess when analyzed by SEM and XRD. The prepared zeolite was employed in the petroleum refinery wastewater treatment to test its organic and inorganic removal efficacies through its COD and Fe content adsorption where it exhibited 99% and 98% efficiency removal respectively.